(untitled) (Journal of Pathology of Nepal, 2019)
Background: Treatment modalities and prognosis of breast carcinoma depend largely on their hormone receptors (Estrogen and Progesterone Receptors) and HER2/neu profile. Various studies conducted within Nepal have highlighted their overall status in breast carcinomas but studies on their correlation with histological grade are few. This study aims to correlate hormone receptors and HER2/neu status with different histological grades of invasive breast carcinoma. Materials and Methods: This is a retrospective analysis of cases received at Intrepid Cancer Diagnostics, Nepal between January 2015 to December 2018 for evaluation of status of hormonal receptors and HER2/ neu on invasive breast carcinomas. Mastectomy and excisional biopsies were included for statistical correlation between hormone receptors, HER2/neu and histological grades (n=364). P-value<=0.01 was considered statistically significant. Results: Of 364 invasive carcinomas categorized into grades 1, 2 and 3, Estrogen Receptor positivity was noted in 77.3% (34/44), 60.8% (115/189) and 28.2% (37/131) respectively; Progesterone Receptor positivity was noted in 61.4% (27/44), 52.4% (99/189) and 21.4% (28/131) respectively; HER2/neu positivity was noted in 18.2% (8/44), 20.1% (38/189) and 19.8% (26/131) respectively. Triple negativity was found to be 9.1% (4/44), 21.7% (41/189) and 41.9% (55/131) in grade 1, 2 and 3 carcinomas respectively. Conclusions: Estrogen and Progesterone receptor expressing carcinomas were found to be more often of grade 1 category, with this rate declining through grades 2 and 3. No such correlation was noted for HER2/neu. Triple negative carcinomas were found to be of higher grade (grade 3).